Detection of ultrafast electron energization by whistler-mode chorus waves in the magnetosphere of Earth - S. Kurita; Y. Miyoshi; S. Saito; S. Kasahara; Y. Katoh; S. Matsuda; S. Yokota; Y. Kasahara; A. Matsuoka; T. Hori; K. Keika; M. Teramoto; et al. (Scientific Reports)
Abstract Electromagnetic whistler-mode chorus waves are a key driver of variations in energetic electron fluxes in the Earth’s magnetosphere through the wave-particle interaction. Traditionally understood as a diffusive process, these interactions account for long-term electron flux variations (> several minutes). However, theories suggest that chorus waves can also cause rapid (< 1 s) electron acceleration and significant flux variations within less than a second through a nonlinear wave-particle interaction. Detecting these rapid accelerations has been a great challenge due to a limited time resolution of conventional particle instruments. Here, we employ an analysis technique to enhance the time resolution of the particle measurements, revealing rapid electron flux variations within less than one second associated with chorus waves. This technique exposes short-lived flux increases significantly larger than those observable with the standard time resolution. Our findings indicate that these transient flux variations result from the nonlinear acceleration of electrons induced by the chorus waves, highlighting the importance of nonlinear wave-particle interactions in creating high energy electrons in the Earth’s magnetosphere. The same acceleration mechanism should operate in the magnetospheres of Jupiter and Saturn where chorus waves are present, and in laboratory plasma environments when chorus-like waves are excited.